2009
DOI: 10.1128/aem.02908-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Biotic Potential of Honeybee Microsporidia

Abstract: The biological cycle of Nosema spp. in honeybees depends on temperature. When expressed as total spore counts per day after infection, the biotic potentials of Nosema apis and N. ceranae at 33°C were similar, but a higher proportion of immature stages of N. ceranae than of N. apis were seen. At 25 and 37°C, the biotic potential of N. ceranae was higher than that of N. apis. The better adaptation of N. ceranae to complete its endogenous cycle at different temperatures clearly supports the observation of the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 14 publications
9
133
0
3
Order By: Relevance
“…Martín-Hernández et al (12) and Higes et al (7) described the higher prevalence of N. ceranaeinfected honeybees in all four seasons, compared with N. apis infection, which is more prevalent in milder seasons such as the spring and autumn. Moreover, Martín-Hernández et al (13) confirmed the different epidemiological patterns between the two species. They found a better adaptation of N. ceranae than N. apis to temperature.…”
supporting
confidence: 51%
“…Martín-Hernández et al (12) and Higes et al (7) described the higher prevalence of N. ceranaeinfected honeybees in all four seasons, compared with N. apis infection, which is more prevalent in milder seasons such as the spring and autumn. Moreover, Martín-Hernández et al (13) confirmed the different epidemiological patterns between the two species. They found a better adaptation of N. ceranae than N. apis to temperature.…”
supporting
confidence: 51%
“…Nevertheless, the facts remain that (i) in Spain and Italy N. ceranae nearly replaced N. apis over the past decade (33) and (ii) N. ceranae infections cause severe honeybee colony losses, at least in Spain (28,30,37). Possible reasons for this assertiveness and virulence of N. ceranae are the exceptional biotic potential of N. ceranae at higher temperatures and the spores' tolerance to temperatures as high as 60°C, combined with resistance to desiccation (18,36). On the other hand, N. ceranae spores have been reported to be sensitive to freezing temperatures (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…In the field, N. ceranae causes an unusual form of nosemosis, which led, and still leads, to severe colony losses in Spain (28,37). One explanation for the higher virulence of N. ceranae in the field could be the better adaptation of N. ceranae than of N. apis to elevated temperatures (18,36), indicating that N. ceranae might be a pathogen whose spread and assertiveness could be influenced by climate change.…”
mentioning
confidence: 99%
“…The higher proportion of immature stages of N. ceranae (70%) than of N. apis (50%) in a comparative study of infected honey bees (Martin-Hernandez et al, 2009) indicated that there are clear differences in the total number of parasites inside the gut. As such, the real number of affected cells in bees cannot be accurately evaluated through the total spore count.…”
Section: 2mentioning
confidence: 99%